Finding Hybrid Solutions to the Financial Management of Customary Land from a Pacific Perspective - Boydell, Spike (The Australian Journal of Indigenous Education, 2008)
Abstract Within contemporary society, customary land is at the nexus of culture and commercialisation. Tasked with facilitating market-based returns on customary land whilst promoting equitable inter and intra-generational sharing of returns, this paper reports a solutions-based research project that investigated and tested a range of hybrid models in the Pacific context. The challenges are diverse, in many cases confronted by the Western approach, which identifies property and ownership as something to address in a businesslike way. Accepting the notion of ongoing Indigenous guardianship of land as sacrosanct and that de Soto's privatisation model is an unacceptable simplification, this paper offers innovative regional examples of customary land administration/management arrangements in encouraging equitable use of customary land by both members and non-members of land “owning” groups. Land is the foundation for the lives and cultures of Indigenous peoples the world over. Without access to and rights over their land and natural resources, Indigenous peoples' distinct cultures, and the possibility of determining their own development and future, become eroded (Jensen, 2004, p. 4).